ANALISIS ASPEK PEMBENTUK BUDAYA K3 DENGAN KEPATUHAN PENGGUNAAN APD PADA PEKERJA PRODUKSI RESIN DI SIDOARJO - Brito, Gregorius Timotius (Universitas Airlangga, 2015)
ABSTRACTThe Ministry of Republic Indonesia launched in 2015 as the national safety culture that every industrial sector was required to implement the safety culture as well. One of the effort to create safety culture in the companies with cultivating the behavior for using personal protection equipment at work. Cooper an expert of safety management explained there were three elements forming safety culture, psychological, behavior, and organization and situation aspect. The main purpose was to analyze the relationship between psychological aspect of workers and organization and a situation aspect with the behavior for using PPE. This is an observational analytic study with cross sectional approach. Data were analyzed with univariate and bivariate. Sample of this research were 25 workers from 32 population that gets by simple random sampling method. Data were collected by questionnaire and observation then analyze in descriptive and use cross tabulating and correlation spearmen test to obtain relationship between variables. The result showed that most of the workers (56%) have low behavior on PPE usage. There almost all workers have a good motivation and clarified that availability and training about PPE was fair. There were significant correlation between motivation and training with complience of using PPE. Higly recommendation for company to increase the motivation for workers by apply a reward system.Keywords: safety culture, behaviour, Personal Protection Equipment